Examining The Sales Performance Of Muslim Fashion SMEs In Central Java-Indonesia: Perspectizing Resource-Advantage (R-A) Theory - Andi Setiawan; Sri Wahyuni; Rif’ah Dwi Astuti; Destine Fajar Wiedayanti; Ana Putri Nastiti; Bagus Yunianto W (Cita konsultindo, 2024)
This study examines consumer behavior in the Indonesian Halal Industry, specifically in Central Java, with a focus on small and medium-sized enterprises (SMEs) in the Muslim fashion sector. The Indonesian market is highly dependent on imported halal products, making it imperative for local SMEs to take advantage of the available opportunities. The objective of this study is to investigate the entrepreneurial orientation of Muslim fashion SMEs and its alignment with market demands to achieve a competitive advantage. To bridge the gap between entrepreneurial orientation and sales performance, the concept of 'Creative Selling Resources' is proposed. Data was collected from 383 Muslim Clothing SMEs in Central Java that have been operational for at least three years. The study's findings highlight the significance of strategic orientation and resource allocation for small and medium-sized enterprises (SMEs) in the Indonesian Halal Industry. Keywords: Entrepreneurial Orientation, Creative Selling Resources, Customer Relationship Performance, Sales Performance, Resource-Advantage (R-A) Theory